Antioxidant Enzyme Activity and Cognition in Obese Individuals with or without Metabolic Risk Factors - Farah, R.; Gilbey, P.; Grozovski, M.; Asli, H.; Khamisy-Farah, R.; Assy, N. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Background: The metabolic syndrome may be associated with cognitive impairment and increased oxidative stress.Aim: To document the association between metabolic syndrome, cognitive impairment and oxidative stress activity in metabolically healthy obese and in metabolically unhealthy obese individuals.Methods: 60 obese individuals aged (49±10 years, 52% male) were enrolled. Obesity was defined as BMI>30. Metabolic syndrome was defined according to ATP III guidelines. Obese individuals were divided into 2 groups: Group 1, metabolically healthy obese (≤2 components of metabolic syndrome), and Group 2, metabolically unhealthy obese (>2 components of metabolic syndrome). Cognitive dysfunction was determined by Montreal cognitive assessment score. Liver Fibro scan (Elastography), Inflammation (CRP), pro oxidants (MDA), antioxidant activity (SOD, PON, GSH, GPx) and insulin resistance (HOMA-IR) were measured.Results: Of the 30 metabolically unhealthy obese individuals, 13% developed dementia, 51% had mild cognitive impairment, and 36% had a normal cognitive score. In the metabolically healthy obese group, 3% developed dementia, 7% had mild cognitive impairment, and 90% had a normal cognitive score. There was a significant difference in liver stiffness (7±3 vs. 5.2±2.7 kpa, p<0.001), liver fat measurement (337±51 vs. 280±20 db/m, p<0.001), MDA (4.7±0.9 vs. 5.47±1.12 mM, P<0.003), Glutathione GSH (27.2±2.4 vs. 28.4±2.3, P<0.03), CRP (9±6 vs. 7±6 P<0.001) and insulin resistance (2.5±1 vs. 6±5.5 p<0.02) between the 2 groups. Correlations were significant between GPx activity and liver stiffness (r=0.37), GPx activity and abdominal girth (r=−0.22) and glucose concentration and SOD activity (r=0.4). Multivariate analysis showed that HOMA-IR, MDA and GSH were the most powerful predictors of metabolically unhealthy obesity.Conclusion: There is a significant mild cognitive impairment and increased oxidative stress activity in the metabolically unhealthy obese. Whether treatment with anti-oxidants improves cognitive dysfunction remains to be determined.
Keywords: antioxidant; metabolic syndrome; healthy individuals; unhealthy; cognition; liver fibro scan